EPIDEMIOLOGY OF ORTHOPEDIC INJURIES IN JIU JITSU ATHLETES - Nicolini, Alexandre Pedro (2020)
Introduction: Jiu-jitsu is an ancient martial art originally from Japan and very common in Brazil, usually known as Brazilian jiu-jitsu. Jiu-jitsu aims to "finish" the opponent through projections, strangulations and immobilizations, which can lead to certain orthopedic injuries with certain particularities such as: type, location and frequency, information that is crucial for prevention and treatment. Objective: This study aims to identify an epidemiological aspect of orthopedic injuries present in jiu-jitsu practitioners. Material and Method: 96 jiu-jitsu practitioners, between 18 and 45 years old, male and female, answered a questionnaire that addressed personal data and history of injuries related to the sport in the last 24 months. Results: 85% of the sample presented injuries related to the practice of jiu-jitsu in the period covered, with an average of 60 days of absenteeism from sports practice. The joints most affected by orthopedic injuries were: fingers, shoulders and knees. Conclusion: orthopedic injuries are quite prevalent in the practice of jiu-jitsu, often distancing athletes from their practice.